Opening Argentina to public-private partnerships: Opportunities and risks for government entities and private investors - Ulrich Schüle; F. Liening-Ewert; D. Schäffer (University of Applied Sciences Mainz, 2018)
Since the presidential elections in November 2015, Argentina's economic system has shifted back to a more neo-liberal paradigm. After more than 15 years of "neodesarrollismo" characterized by large scepticism towards inward FDI, the country opens up to international investment into infrastructure. With a new law adopted in early 2017, Argentina promotes public-private-partnership (PPP) projects. The expectations in Argentina vary from the belief that inward FDI will significantly contribute to the modernization of infrastructure to the fear that PPP projects will surrender the country to the interest of international capital. Even though the government believes that the ambitious National Infrastructure Plan with intended investment of US-69bn in transport and energy infrastructure cannot be achieved without PPP projects, a critical analysis of the conditions under which PPP projects may be successfully applied in Argentina, is yet missing. In order to identify such conditions, a triangulation of three research methods was chosen: First, cases in Europe and Latin America were analysed in order to identify key success factors and arrangements correlated with project deficiencies. The focus was on contractual arrangements of risk distribution between stake holders and impediments to cash flow analysis. Second, documentary analysis was applied to examine the regulatory and institutional environment in Argentina. Third, in-depth interviews with 22 experts from Europe and Latin America were conducted. The experts represented the major stake holders in PPP projects: officials from government procurement, lawyers, bank representatives, and managers of project companies and major suppliers. As a result, conditions for a successful application of the PPP concept in Argentina's road and underground railway infrastructure as well as in integrated waste management systems were derived. The research was carried out in the framework of a bi-national Master program in International Business run by the Hochschule Mainz (Germany) and UCES, Buenos Aires.
Additional information: Paper presented at the 5th Annual International Conference on Business, Law & Economics, Athens, May 7th - May 10th, 2018.
Keywords: 330; Public-Private-Partnership (PPP); risk allocation; Argentina; infrastructure; FDI; multiple case study